Diseño de un banco experimental de bombeo para el análisis de altura neta positiva de succión en bombas centrífugas - Lema Jami, Byron Oswaldo (2022)
The current research work had as aim to implement an experimental bench for the net positive suction head analysis in centrifugal pumps, this project was based on the scientific method starting with the research on pumping systems and the variables, what influence system pumping, the variables measurement was performed by means a thermometer and pressure and flow sensors to get precise data, and later, with the PLC LOGO Siemens conditioning and the programming in an instrumentation software, the acquisition and data visualization. The tests were performed at different revolutions by means frequency variation and with the acquired data of flow rate, discharge pressure and vacuum pressure, the graphs H (m) vs Q (m3/h) and NPSH (m) vs Q (m3/h). These graphs determine, what the pump catalog characteristics curves do not coincide with the got experimental data, since according to the equipment plate, the maximum pumping head is 20.5 m, but in the experimentation is reached a maximum flow 15 m3/h at 60 Hz and a maximum head of 15 m at 60 Hz, 11 m at 50 Hz and 7 m at 40 Hz were reached. The available NPSH experimentation was made with the valve´s manipulation located in the suction and in the discharge, which have the purpose of forcing the cavitation in the pump and it was got the graphs at 60 Hz, 50 Hz and 40 Hz what are related to the required NPSH from the catalog curve.